Mindfulness-Based Program Embedded Within the Existing Curriculum Improves Executive Functioning and Behavior in Young Children: A Waitlist Controlled Trial - Janz, Philip; Dawe, Sharon; Wyllie, Melissa (Frontiers in Psychology, 2019)
There is a growing evidence base for mindfulness-based interventions in educational settings. Notably, there has been little investigation of the potential benefits of classroom-based mindfulness programs in children in the early school years (Preparatory/Kindergarten, Grades 1 and 2) despite early childhood being a period characterized by the development of self-regulation and executive functions. The present study investigated the effects of a mindfulness program that was embedded within a school curriculum. This waitlist controlled trial investigated the effects of a mindfulness program, CalmSpace, delivered by classroom teachers across two school terms. A total of 55 students, Mage = 76.4 months, SD = 8.62, were allocated to participate in CalmSpace in Terms 3 and 4. Thirty-six students in the waitlist control condition, Mage = 80.53 months, SD = 13.04, participated in the intervention in Term 4. The start of Term 3 served as baseline (Time 1), and measures were obtained at the end of Term 3 (Time 2) and the end of Term 4 (Time 3). Direct measures of executive functioning using the Flanker Inhibitory Control and Attention Test (Flanker Task) and Dimensional Change Card Sort Task (DCCS) from the National Institute of Health Toolkit were obtained. Teachers’ report of children’s behavior was also obtained using the Strengths and Difficulties Questionnaire (Teacher version) at the beginning and at the end of Term 3, and at the end of Term 4. Children who received the CalmSpace program showed improvements on the DCCS relative to waitlist control at Time 2 (Cohen’s d = 0.48) and Time 3 (Cohen’s d = 1.10). Similar results were found on the Flanker Task with greater improvements found at Time 2 (Cohen’s d = 0.77) and Time 3 (Cohen’s d = 1.33). Teachers reported improvements for those receiving CalmSpace at Time 2 on total SDQ scores, Emotional Symptoms, Conduct Problems, Hyperactivity/Attention (Cohen’s d = 0.32, 0.14, 0.46, 0.30, 0.33, and 0.53, respectively) compared to waitlist control and at Time 3 (Cohen’s d = 0.85, 0.37, 0.48, and 0.90, respectively). The findings demonstrate that implementing the CalmSpace program can lead to improvements in EF and attention for young children. Despite limitations, this study provides promising evidence that the inclusion of focused, targeted mindfulness activities throughout the day may represent a value-added component to the regular school curriculum that can result in benefits for the students.